Layanan Bimbingan Konseling Perencanaan Individual untuk Menumbuhkan Motivasi Belajar Siswa - Enung Hasanah; Ayu Yusaeni (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
The role of guidance and counseling teachers in schools is vital in increasing student learning motivation, especially for students experiencing personal and learning problems. The existence of counseling guidance for teachers in each school functions to foster student personality, improve student learning motivation, and overcome student learning problems so that they can become independent students. This study aims to find out: How does the guidance and counseling service build student motivation to learn based on the student's point of view? The research method used is the phenomenological research method. The data collection method was carried out through individual interviews, with the interview duration between 30-45 minutes per person. Data management is carried out using thematic qualitative analysis methods. The results showed that individual planning essential services could assist students in growing motivation to learn because students feel they understand more about the picture of future developments, students feel they have friends to tell stories, students think they get additional insight about scholarships, and students feel they get solutions to individual problems.